Endurance testing of engineering model additive-manufactured high temperature resistojets made from Inconel 625 and tantalum - M. Robinson; F. Romei; C. Ogunlesi; D. Gibbon; A. Grubišić; S. Walker (Materials & Design, 2022)
This paper reports endurance tests on engineering model high-temperature resistojets manufactured using flight-representative materials. High-temperature resistojets improve the economics of small satellites and are an attractive technology for auxiliary propulsion on all-electric geosynchronous satellites. Additive manufacturing was used to economically produce the geometrically complex heating element. Endurance tests were performed on heaters and full thruster assemblies. Eight engineering model thrusters were tested, with five manufactured from Inconel 625, and three having a tantalum heater and nozzle operating at higher temperatures. The eight units were operated in vacuum to determine their endurance. The Inconel thrusters were operated at 30 W electrical power, while the tantalum thrusters were operated at 60 W, representative of intended operating conditions. Measurements of temperature and electrical resistance throughout the tests were used to infer the condition of the thrusters. Following a retrofit of two of the Inconel 625 thrusters with a modified component to mechanically support the heater, they completed 6000 heating cycles without failure. The tantalum thrusters, equipped from the outset with the modified component, completed 10000 heating cycles. Both variants exceeded the minimum cycle requirement of 4000. This work demonstrates the operational feasibility of additive-manufactured, high-temperature resistojets.